Surfactant Protein B Deficiency Caused by Homozygous C248X Mutation-A Case Report and Review of the Literature - Stefan Kurath-Koller; Bernhard Resch; Raimund Kraschl; Christian Windpassinger; Ernst Eber (Thieme Medical Publishers, Inc., 2015)
Abstract Objective Surfactant protein B (SP-B) deficiency is a rare autosomal recessive disorder that is usually rapidly fatal. The c.397delCinsGAA mutation (121ins2) in exon 4 is found in more than two-thirds of patients. Design We report on a fatal case of SP-B deficiency caused by a homozygous C248X mutation in exon 7 of the SP-B gene. In addition, we provide an update of the current literature. The EMBASE, MEDLINE, and CINAHL databases were systematically searched to identify all papers published in the English and German literature on SP-B deficiency between 1989 and 2013. Results SP-B deficiency is characterized by progressive hypoxemic respiratory failure generally in full-term infants. They present with symptoms of respiratory distress and hypoxemia; chest X-ray resembles hyaline membrane disease. Prenatal diagnosis is possible from amniotic fluid or chorionic villi sampling. Conclusion Thirty-four mutations have been published in the literature. Treatment options are scarce. Gene therapy is hoped to be an option in the future.